(untitled) (MATEMATIKA, 2018)
In this paper we present a new concept called time-neutrosophic soft expert set (T-NSESs). We also de¯ne its basic operations, namely complement, union, intersection, AND, OR and study some of their properties. We give examples for these concepts. Finally we present an application of this concept in a decision-making problem.